An analysis of the carboxylate stretching vibrations in some Cu(II) complexes of amino acids - Baran, Enrique José (2014)
The behavior of the stretching vibrations of the carboxylate groups in twenty one Cu(II) complexes of amino acids (aa) of general composition Cu(aa)2 or Cu(aa)2.nH2O is analyzed on the basis of previously reported vibrational spectroscopic data and on the structural characteristics of these complexes. Some general trends are pointed out and discussed. In all cases, the spectroscopic results are consistent with the monodentate binding of the COO- groups with the metal center. Brief comments on the spectroscopic behavior of the carboxylate groups in a series of polymeric Cu(II) complexes of dipeptides are also presented.